Analysis of The Cancer Genome Atlas data to determine the correlation between AGO2, TERT, and TERC in various cancers - Jung, Soo-Jung; Lee, Jae-Ho (Translational Cancer Research, 2019)
We read with great interest the article by Laudadio et al. (1) regarding the role of AGO2 in telomere biology; their study asserted that AGO2 regulated telomerase activity through the control of the association between TERT and TERC in the assembly of active telomerase ribonucleoprotein.